(untitled) (Bulletin of criminological association of Ukraine, 2024)
The modern practice of combating cross-border terrorist activity is impossible without the active use of knowledge in the financial sphere. Algorithmization of the procedure for carrying out financial investigations for the detection of terrorist criminal offenses is an established and effective competence that ensures the official detection and termination of this type of crime, as well as prevents their commission. However, today this functionality is actually outside the scope of legal regulation, as it is not regulated by domestic legislation and is not properly regulated at the level of departmental (sub-legal) legal acts. The article examines the mechanisms of conducting financial investigations during the documentation of terrorist criminal offenses. The essence of financial investigations, including parallel ones, was revealed; generalized and systematized forms of conducting financial investigations. Based on the analysis of financial documents of various terrorist organizations and FATF reports, the main directions of using financial resources for terrorist activities are highlighted. The structure and powers of state agencies that assist law enforcement agencies in conducting financial investigations are defined; the system of international organizations whose activities are aimed at ensuring the detection of financial violations is investigated. The work presents the foreign experience of conducting specialized investigations for the possibility of its application in domestic practice. The advantages of conducting financial investigations during the pre-trial investigation of terrorist criminal offenses are highlighted and substantiated. The article emphasizes the imperfection of the mechanism of financial investigations, since the legislator did not pay attention to, in particular, questions regarding the definition of the concept of "financial investigation", as well as criminal offenses, the investigation of which requires the mandatory use of financial investigation methods, including parallel . The author proposed relevant changes to the thematic legislation of Ukraine, aimed at eliminating the existing legal uncertainty. This, in turn, will allow the law enforcement system of Ukraine to successfully fulfill FATF requirements and integrate into the legal environment of the developed countries of the world.